KAJIAN PERSEPSI NELAYAN TERHADAAP KEBIJAKAN PERIKANAN DI KOTA BENGKULU - Ningsih, Fina Sulistya; Cahyadinata, Indra; Irnad, Irnad (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2017)
Perception is the ability of a person to organize an observation, was one may have different perceptions even with the same object. In this research will analyze how the perception of fisherman society toward fishery policy in Bengkulu city. The study was conducted in Bengkulu City, namely Pasar Bengkulu, Pondok Besi and Malabro. The number of samples in this study were 114 respondents. Data analysis using linkert scale with 5 criteria. The result shows that the perception of fishermen community on the provision of aid in the form of fish catching infrastructure is 14.91% stated very good, 42.98% good, 25.44% good enough, 8.77% not good and 7.89% very bad. The perception of fishermen community on the provision of aid in the form of fish catching processing facilities as much as 6.14% is very good, 27.19% good, 39.47% good enough, 20.18% is not good and 7.02% is not very good and the last perception of fishermen community on the training and Marketing of fish catch shows that 20.18% states very good, 18.42% good, 26.32% good enough, 27.93% is not good and 13.15% is not very good.If the overall conclusion of average fisherman's perception on policy is 13.73% fisherman society is very perceived Good, 29.53% good perception, 30.41% good enough, 16.96% is not good and 9.35% fisherman society perceived is not very good. It can be concluded that most people perceive to agree on fishery policy in Bengkulu City.